2016
DOI: 10.1111/hdi.12408
|View full text |Cite
|
Sign up to set email alerts
|

Lower C‐reactive protein and better hemodialysis survival are associated with regular exercise activity: Longitudinal outcomes from the ACTIVE‐ADIPOSE special study

Abstract: Introduction Cross-sectional and longitudinal studies in the general population have shown that a physically active lifestyle may have anti-inflammatory properties, but evidence from studies conducted with maintenance hemodialysis (HD) patients is limited. Methods A multicenter prospective cohort of 755 HD participants aged 20-92 was evaluated in a USRDS special study 2009-2013. Kilocalories/week (kcal/week) of leisure time physical activity (LTPA) was estimated from the Minnesota Leisure Time Activity questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Cross-sectional and longitudinal studies in the general population have shown that a physically active lifestyle may have anti-inflammatory properties, but evidence from studies conducted with maintenance HD patients is limited. In a previously reported multivariable analysis using data for the full AAS cohort age ≥18, adjusted for participant age, we found that non-sedentary behavior was associated with lower log-normalized CRP over 24 months ( 13 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Cross-sectional and longitudinal studies in the general population have shown that a physically active lifestyle may have anti-inflammatory properties, but evidence from studies conducted with maintenance HD patients is limited. In a previously reported multivariable analysis using data for the full AAS cohort age ≥18, adjusted for participant age, we found that non-sedentary behavior was associated with lower log-normalized CRP over 24 months ( 13 ).…”
Section: Discussionmentioning
confidence: 86%
“…An individual who expends <500 kcal/week in LTPA over a 7-day period can be considered sedentary, and the cut point of 500 kcal/week therefore provides a metric for identifying participants with less active vs. more active behavior and lifestyle ( 12 ). Participants with <500 vs. ≥500 kcal/week estimated LTPA energy expenditure were classified as demonstrating a sedentary vs. non-sedentary profile at baseline and at 12- and 24-month follow-ups ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have con rmed that exercise could bring dialysis patients with better exercise capacity [3], physical function [4,17,31], sleep quality [4], nutritional status [31], psychological status [10], quality of life [10,31], and better hemodialysis survival [11]. Exercise ways in MHD patients can be divided into three major types, including aerobic exercise, resistance exercise and a combination of aerobic exercise and resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training, as a type of physical activity, has been shown great bene ts for MHD patients. Suitable and regular exercise can improve their physical function, nutritional status, psychological status, survival rate and QOL [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%